Population distribution in coastal of Linhares-ES - Gonçalves, Felipe Pinto (Geografares, 2014)
The article analyzes the distribution of population in the coastal districts of the municipality of Linhares-ES. At first, the coastal quota is contextualized in relation to the total population. Then, a retrospective of the peopling of the districts is presented. Finally, from the analysis of orthophotos, field observations and statistical data, are characterized forms of organization of housing and areas of population distribution. It is observed that most of the population is located in the coastal frontage, predominantly concentrated in villages and urban and rural settlements.
Keywords: Linhares; Coastal population; Distribution